Prescribing Patterns and Outcomes of Edoxaban in Atrial Fibrillation Patients From Asia - One-Year Data From the Global ETNA-AF Program - Choi, Jong-Il; Kiatchoosakun, Songsak; Jiampo, Panyapat; Tse, Hung Fat; Soo, Yannie Oi Yan; Wang, Chun-Chieh; Lee, Chang Hoon; Pecen, Ladislav; Unverdorben, Martin; De Caterina, Raffaele; Kirchhof, Paulus (Circulation reports, 2024)
Background: This study reports prescribing patterns and the 1-year effectiveness and safety of edoxaban in an Asian cohort of Edoxaban Treatment in routiNe clinical prActice (ETNA)-Atrial Fibrillation (AF) patients. Methods and Results: The Global ETNA-AF program integrates prospective, observational, noninterventional regional studies, collecting data on characteristics and clinical outcomes of patients with AF receiving edoxaban for stroke prevention. Baseline characteristics, medical history, and 1-year clinical event rates were assessed in patients from South Korea, Taiwan, Hong Kong, and Thailand. Clinically relevant events assessed at 12 months included all-cause death, cardiovascular death, ischemic and hemorrhagic stroke, systemic embolic events (SEEs), bleeding, and net clinical outcome (NCO). Overall, 3,359 patients treated with edoxaban 60 or 30 mg once daily completed 1-year follow-up; 70.9% of patients received recommended dosing according to local labels. Baseline mean±standard deviation age was 71.7±9.6 years, CHA2DS2-VASc score was 3.1±1.5, and modified HAS-BLED score was 2.3±1.1. Mean age and sex were similar across countries/regions. The 1-year event rate for all-cause death was 1.8%; major bleeding, 1.3%; ischemic stroke, 1.1%; cardiovascular mortality, 0.7%; hemorrhagic stroke, 0.3%; SEEs, 0%; and NCO, 4.1%; with differences observed between countries/regions and dosing groups. Conclusions: Most Asian patients with AF were prescribed recommended edoxaban dosing in routine care settings. At 1-year follow-up, this analysis supports the effectiveness and safety of edoxaban in these patients.
Keywords: Oral anticoagulation; Dosing; Asia; Atrial fibrillation; Edoxaban